2018
DOI: 10.1007/s10661-018-6531-8
|View full text |Cite
|
Sign up to set email alerts
|

Industrial point source CO2 emission strength estimation with aircraft measurements and dispersion modelling

Abstract: CO2 remains the greenhouse gas that contributes most to anthropogenic global warming, and the evaluation of its emissions is of major interest to both research and regulatory purposes. Emission inventories generally provide quite reliable estimates of CO2 emissions. However, because of intrinsic uncertainties associated with these estimates, it is of great importance to validate emission inventories against independent estimates. This paper describes an integrated approach combining aircraft measurements and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…The study was limited to comparing the approaches used with API without generating risk or forecast maps to determine pollution. Carotenuto et al (2018) employed two methods to analyse the intensity of CO 2 emissions from an industrial point source in Biganos, France. The first one was a mass balance method based on aircraft observed data, and the second was a dispersion simulation approach incorporating the CALMET diagnostic meteorological model and the CALPUFF puff dispersion model.…”
Section: Gaussian Plume Modelmentioning
confidence: 99%
“…The study was limited to comparing the approaches used with API without generating risk or forecast maps to determine pollution. Carotenuto et al (2018) employed two methods to analyse the intensity of CO 2 emissions from an industrial point source in Biganos, France. The first one was a mass balance method based on aircraft observed data, and the second was a dispersion simulation approach incorporating the CALMET diagnostic meteorological model and the CALPUFF puff dispersion model.…”
Section: Gaussian Plume Modelmentioning
confidence: 99%
“…Furthermore, inventory comparison analysis is impossible at the urban scale due to the lack of a detailed emission inventory. The studies developed different uncertainty metrics and tools such as PDFs, the bootstrap sampling method, fuzzy mathematics, the 95% Cis, and relative uncertainty [54][55][56][57], which could provide the reference for our workflow. Moreover, some studies which retrieved CO 2 emissions using atmospheric models used data assimilation technologies in an attempt to estimate and reduce the uncertainty in CO 2 emissions [53,58].…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Some studies offer an algorithm available in CALPUFF, a new model for regulating dispersion, which might calculate concentrations with high precision by accounting for upwind meandering near a source (Barclay and Borissova 2013). However, CALPUFF cannot offer reliable near-field concentration measurements from sources responsible for modern emissions if plume spreads are measured using estimates of turbulent velocities near to sources (Carotenuto et al 2018). This study, designed to formulate a refined modeling perspective for near field application for regulation, used a case study approach, and the evaluation of its result showed a corresponding agreement with the literature.…”
Section: Gaussian Plume Modelingmentioning
confidence: 99%